A Review of Enterprise Architecture for Strategic Performance Management in the Transportation Sector Digital Transformation (Open International Journal of Informatics, 2023)
This paper reviews the use of Enterprise Architecture (EA) for strategic performance management in the transport sector's digital transformation, focusing on the Balanced Scorecard (BSC) theory.  EA is essential for strategic planning and performance management in the transport industry, which is vital to the economy.  The study analyses academic publications, industry reports, and case studies to assess EA's benefits, drawbacks, and novel solutions in transportation.  The Balanced Scorecard framework, which measures and manages performance holistically, should be used to align EA projects.  EA and the Balanced Scorecard theory may provide a solid foundation for strategic performance management in the transportation sector's digital transition.  It aligns goals, objectives, and KPIs with strategic vision and mission.  EA also helps identify important capabilities, processes, and IT systems to accomplish desired results.  It also improves decision-making by offering an integrated perspective of the organisation's resources, capabilities, and dependencies.  In the transportation industry, EA for strategic performance management faces obstacles, including imprecise communication, insufficient governance, and limited planning.  Innovative solutions, including improved communication channels, stronger governance systems, and enhanced planning techniques, are recommended to tackle these issues.  This review analysis sheds light on the transport sector's digital transition using EA and the Balanced Scorecard theory.  It advises researchers, practitioners, and policymakers to use EA to improve performance management and maintain transportation industry growth.
Keywords: Enterprise Architecture; Intelligence Transportation System; Review Paper; Transportation